Os processos educomunicativos da rádio comunitária Capixaba de Capixauã, Santarém (PA) - Silva, Matheus Macedo Fernandes da (2022)
The study investigates the importance and contributions of edu-communication and community communication initiatives for social inclusion and democratization of communications in the community of Capixauã in the Tapajós/Arapiuns Extractive Reserve in the municipality of Santarém (PA). The research analyzed how the educomunicative processes occurred in the implementation and development of the community radio Capixaba by ONG Saúde & Alegria, in addition to ascertaining the reasons that contributed to the interruption of its activities. Regarding the methodological procedures of data collection we used bibliographical research on topics such as human development, community communication, edu-communication, communication for development and other issues related to the theme. The research was carried out to listen to the residents and understand the communicative process that involved Capixaba radio analyzing the history of before, during and the end of the radio. The field research was directed by semi-structured interviews and with active observation in the field. In the discourses of the research authors, a high degree of social engagement in the construction and development of radio was evidenced, as well as a feeling of belonging and inclusion of a community in a condition of social vulnerability. During years of operation, the Radio Capixaba contributed to the digital inclusion and democratization of communication, in addition to giving voice to one of the many traditional communities of the Amazon. (AU)